Mental Health and Coping in Daily Life – Survey with Adults in Western Finland - Salminen-Tuomaala, Mari; Tuuri, Hannu; Katajavirta, Marja; Nissinen, Kaija (European Journal of Applied Sciences, 2025)
The purpose of this quantitative survey was to report data on adult respondents’ self-rated mental health and coping in a region in the west of Finland. The study is part of a larger research project on health and health-related choices, thinking and behaviour patterns. Questionnaires were sent by post to people picked through random sampling from the Digital and Population Data Register. The respondents could choose to reply by post or using an online survey tool. The data were analyzed using IBM SPSS Statistics 29 software. The number of respondents was 461 and the response rate was 23.1%. The perceived mental wellbeing was better in the oldest age group, compared to the youngest age group. The younger respondents more commonly lived with depression, anxiety or other mental health problem. Single alone-living people rated their mental wellbeing as lower compared to the older or married/cohabiting respondents. Higher education was associated with better experienced mental health.